2021
DOI: 10.1038/s41598-021-94907-w
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic significance of serum angiopoietin-1 and -2 concentrations in patients with pulmonary hypertension

Abstract: Several biomarkers for detecting pulmonary hypertension (PH) have been reported. However, these biomarkers are deemed insufficient to detect PH in its early stages. We evaluated the utility of serum angiopoietin (ANGP), a glycoprotein related to angiogenesis, as a diagnostic and prognostic biomarker of PH. Patients with PH who underwent right-heart catheterization, were retrospectively studied. Serum concentrations of ANGP-1 and ANGP-2 were measured using an enzyme-linked immunosorbent assay in patients with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This was necessary as platelet-free plasma required by available assays could not be obtained from the current cohort. Nonetheless, previous studies have reported significant differences in serum angpt-1 concentrations between comparator groups demonstrating that serum is a suitable medium for investigating angpt-1 expression [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was necessary as platelet-free plasma required by available assays could not be obtained from the current cohort. Nonetheless, previous studies have reported significant differences in serum angpt-1 concentrations between comparator groups demonstrating that serum is a suitable medium for investigating angpt-1 expression [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, elevated levels of VEGF have been associated with vascular smooth muscle cell proliferation in a mouse model of hypoxic PH ( Liu et al, 2018 ). High concentrations of Ang-2 and bFGF have been identified as significant poor prognostic factors in PH ( Seyfarth et al, 2015 ; Enomoto et al, 2021 ). It can be seen that there is a close relationship between HPA and pulmonary artery endothelial cells.…”
Section: The Role Of Hpa In the Development Of Phmentioning
confidence: 99%
“…Kumpers et al showed that ANG2 was statistically significantly correlated with CI, PVR, and mvSatO 2 , confirming its involvement in the pathogenesis of IPAH [ 88 ]. However, additional information has emerged more recently, suggesting that ANG2 is not associated with treatment response in patients with IPAH [ 89 ], although it may be used as a diagnostic and prognostic marker in Group 3 patients with PH.…”
Section: Endothelial Cell Dysfunction and Pulmonary Arterial Smooth M...mentioning
confidence: 99%